Callus induction and regeneration of Alkanna orientalis var. Orientalis and A. sieheana - Yaman, Cenney; Uranbey, Serkan; Ahmed, Hussein Abdullah; Özcan, Sabahattin; Tugay, Osman; Başalma, Dilek (Bangladesh Journal of Botany, 2019)
Callus induction and proliferation of Alkanna orientalis var. orientalis and Alkanna sieheana containing valuable alkannin/shikonin (A/S) derivates were investigated using leaf base and stem segment explants. Stem segments and cotyledonary leaf base of both species were cultured on Murashige and Skoog medium fortified with different concentrations of BAP, Kn, NAA, IAA and IBA for callus induction and shoot regeneration. High frequency reproducible, prolific and compact calli formation was obtained from the stem segments of both species in all media tested. The frequency variations of callus induction and shoot regeneration were discussed in terms of different species, plant growth regulators and explant resources. A. orientalis and A. sieheana may be considered to be alternative plants for the A/S production in vitro.